Optimisation of the squeeze forming process - Ahmad, Rosli (2006)
This thesis presents the optimisation of the squeeze forming process, considering both the thermal and mechanical aspects. The Finite Element Method has been used to simulate the process and a Genetic Algorithm was used as an optimisation tool. The thermal optimisation has been applied to the squeeze f0Il11ing process to achieve near simultaneous solidification in the cast part. The positions of the coolant channels were considered as design variables in order to achieve such an objective. The fOllllulation of the objective functions involved two points and also considered the whole domain. The validation aspects of the optimisation of the casting processes for 2D and axi-symmetric problems were presented. The influence of the interfacial heat transfer coefficient related to optimisation of the process was explored. For the multi-objective optimisation problem, the objective was to achie\'e ncar simultaneous solidification in the cast part and also near unifoIl11 \'on ivlises stress distribution in the die for the first and also tenth cycles. This is because it has been found that the process starts to reach cyclic stabilisation after the tenth cycle. The comparison II between the design obtained froin the practical solution derived from the optimisation process and also the design which has been applied in industry was also discussed. The Design Sensitivity Analysis and Design Element Concept have been applied to the squeeze f0Il11ing process. For parameter sensitivity analysis, the Youngs Modulus was considered as a design variable. A few design element subdivisions have been employed to explore its application to the process. For shape sensitivities involving the coolant channels, the parametelisation was required in order to consider the coolant channel as an entity. The extent to which the tendency to move the coolant channel either in the X or Y -direction with respect to the particular von Mises stress constraint in the die was also discussed.